See finish! Scunnered!! A vernacular critique of hierarchies of knowledge in marketing. (June 2022) - Bádéjọ, Folúké A.; Gordon, Ross
Our paper presents a critique of how a totalising consumer voice predominates, as does a globalised marketing knowledge. We argue that it is time to release ideas from the marginalised, the unhinged and the peripheral. We feature a fictional dialogue between two characters using vernacular language: Ọmọ Naija, a Pidgin-speaking Yorùbá woman from Nigeria, and Rab, a Glasgow Patter-speaking man from Scotland. The conversation traverses two important areas of critique regarding hierarchies of knowledge in marketing: (1) decolonisation and (2) marginalisation of the vernacular. Our characters draw upon ancient and contemporary thinkers, writers and cultural icons to substantiate their critiques. Our analysis foregrounds how hierarchies of knowledge in marketing serve academic imperialism, an untranslatability of vernacular life and ignore the terroir of everyday existences.